Dialektika Metodologis antara Otoritas Rawi dan Validitas Teks dalam Bingkai Naqd Al-Hadis: Methodological Dialectics Between the Authority of Rawi and Textual Validity Within the Framework of Naqd al-Hadith - Azizah Fauziyah Hamid; Muhammad Yahya; Abdul Rahman Sakka (AL ISNAD: Journal of Indonesian Hadith Studies, 2026)
Discussions about the authority and authenticity of hadith remain a crucial discourse in the dynamics of Islamic thought, especially when faced with modern realities. In this article, we analyze the methodological dialectic between sanad criticism and matan criticism as integrative instruments in determining the validity of hadith accounts. By applying qualitative methods through literature research, this article seeks to dissect the relationship between biographical-historical and substantive-rational aspects. The results show that sanad and matan criticism are not two separate entities, but rather a complementary epistemological unity. A study of the hadith on female leadership serves as evidence that methodological dialectics can render a text that is formally considered sahih (authentic) as temporal through siyaq al-wurud analysis. The implication of this article lies in the assertion that traditional hadith criticism methodology has vitality as a framework for religious digital literacy to filter disinformation and decentralize authority in the contemporary era. Therefore, this finding offers a paradigm that the authenticity of hadith does not only rely on the integrity of transmission, but also on the coherence of the text with the universal principles of Islam and the developing sociological reality.